Patterns in Mongolian nomadic household movement derived from GPS trajectories. (September 2020) - Teickner, Henning; Knoth, Christian; Bartoschek, Thomas; Kraehnert, Kati; Vigh, Melinda; Purevtseren, Myagmartseren; Sugar, Munkhnaran; Pebesma, Edzer
Abstract: This paper presents an approach for a quantitative analysis of movement patterns of nomadic households based on GPS trajectories. We distributed GPS loggers to 400 Mongolian herder households who carried them over a 9-month period, continuously recording position data every 30min. A total of 142of the resulting trajectories fulfilled our data quality criteria and were considered during the analysis. Based on this data, we derive summary indicators describing key parameters of the households' mobility including measures of distance and number of movements as well as shape characteristics of the trajectories. We conduct an explorative statistical analysis of these summary indicators to investigate patterns in the nomadic mobility. We identify three movement strategies based on the number of different campsite locations and the distances traveled between campsites. We also compare the results to the existing literature on the mobility of Mongolian herders. Our findings show that GPS-based studies present a suitable framework to quantitatively analyze different movement strategies of nomadic herders. Highlights: We propose a concept for collecting and analyzing nomadic GPS trajectories. Mongolian nomadic herders differ gradually in their movement characteristics. They mainly adopt two strategies to cover larger distances. We discuss potential applications and recommendations for future GPS-based studies.